Gambaran Kepercayaan Masyarakat Pesisir saat Masa Kehamilan Hingga Masa Nifas di Wilayah Batang Kilat Kecamatan Medan Labuhan Tahun 2023 - Nurhayati, Nurhayati; Lubis, Amru Prabowo; Prasetyo, Agung; Purba, Fadila Syahrani; Puspitasari, Inda; Purba, Nurul Fitriani; Keysah, Shindu; Maimuna, Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Various cultures during pregnancy during Sanifas still appear in society in the form of various prohibitions and behaviors that cannot be carried out by mothers during pregnancy and the postpartum period. The Batang Kilat area, Medan Labuhan District, is one of the modern coastal areas, so it is necessary to study cultural practices during pregnancy to the postpartum period in this area. The purpose of this research is to explore the beliefs and cultural practices in the Batang Lightning region during pregnancy to the postpartum period. This research is a qualitative research with a case study. In-depth interview data collection method. Participants in this understanding are pregnant women and postpartum women with a total of 7 participants. The results of this study obtained 5 themes, namely views regarding pregnancy examination and care, views regarding birth attendants, views regarding dietary restrictions and behavior during pregnancy, views regarding behavior during the postpartum period, and family support in postpartum care. Keywords: culture, childbirth, belief, pregnancy